1964
DOI: 10.1177/001872086400600104
|View full text |Cite
|
Sign up to set email alerts
|

Performance Decrement under Psychological Stress

Abstract: for additional information. This is an Open Access journal. This means that it uses a funding model that does not charge readers or their institutions for access. Readers may freely read, download, copy, distribute, print, search, or link to the full texts of articles. This journal is covered under the CC BY-NC-ND license.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

1967
1967
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 2 publications
1
12
0
1
Order By: Relevance
“…If to crash, and having the ,ubjects fill out a checklist on the way down (see Berkun, 1964). Others have examined parachuting (Burke, 1980,;1ammerton and Tickner, 1969), cr other dangerous situations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If to crash, and having the ,ubjects fill out a checklist on the way down (see Berkun, 1964). Others have examined parachuting (Burke, 1980,;1ammerton and Tickner, 1969), cr other dangerous situations.…”
Section: Resultsmentioning
confidence: 99%
“…flight emergency training (Dougherty, Houston, & Nickles, * 1957;Smode, Hall, & Meyer, 1966), performance decrements (Berkun, 1964;ern., 1966). and combat (Kubala & Warnick, 1979).…”
Section: )mentioning
confidence: 99%
“…Performance has been shown to be impaired by a variety of stressors such as high noise (Broadbent, 1978;Poulton, 1978), increased workload (Goldstein & Dorfman, 1978), crowding (Hayduk, 1983;Schmidt & Keating, 1979), performance pressure (Baumeister, 1984;Baumeister & Steinhilber, 1984), psychological stress (Berkun, 1964), and anticipatory threat of shock (Wachtel, 1968). In operational performance studies, Villoldo and Tarno (1984) have reported that performance stress alone can cause increased errors while Idzikowski and Baddeley (1983) have reported that the time taken to complete manual tasks will double under conditions of high stress.…”
Section: Stress and Performancementioning
confidence: 99%
“…In addition, research has examined diving emergencies (Radloff & Helmreich, 1972), flight emergency training (Dougherty, Houston, & Nicklas, 1957;Smode, Hall, & Meyer, 1966), performance decrements (Berkun, 1964;Kern, 1966), and combat stress (Kubala & Warnick, 1979).…”
Section: 4mentioning
confidence: 99%